Book Review: K.S. Subramanian, State, Policy and Conflicts in Northeast India. (December 2016) - Dutta, Akhil Ranjan
K.S. Subramanian, State, Policy and Conflicts in Northeast India. New Delhi: Routledge. 2016. 213 pages. ₹795.